Burkina Faso : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2013)
The number of Malian refugees in Burkina Faso has increased, but the government's contribution remains in line with earlier estimates. Growth for 2012 has been revised upward to 8 percent. The overall fiscal deficit is significantly lower than anticipated. The current account is expected to improve next year. There is significant improvement in revenue collection. The authorities are stepping up efforts to improve resilience to shocks. Efforts are under way to improve debt management capacity. The mining taxation regime needs to rebalance the interests of investors.